THE EFFECT OF GAMMA IRRADIATION AND SODIUM AZIDE ON GERMINATION OF SOME RICE CULTIVARS - Bagus Herwibawa; Totok Agung Dwi Haryanto; Sakhidin Sakhidin (AGRIVITA Journal of Agricultural Science, 2014)
Efforts to increase rice production through genetic improvement are often limited by the availability of natural diversity. That natural diversity can be improved through induced mutation. Selected characters can be observed since the germination phases, which may also indicate the plants survival under field conditions. Experimental design was arranged in split plot, with cultivars as main plot and mutagen doses as sub plot. The experiment consisted of 36 treatment combinations, with each treatment consisting of 10 replications. Data were recorded on percentage of first count, final count and germination rate. The data were analyzed using F-test by SAS 9.0 and mean separation was carried out by employing DMRT at 95 % (α = 5 %) of confidence level. The results showed that the best cultivar response for germination traits was Inpari 13, the best mutagen to build cultivar for germination traits was Gamma 150 Gy, and the best combination between cultivar and mutagen for germination traits was Inpago Unsoed 1 that was treated with Gamma 150 Gy. Keywords: gamma irradiation, germination, rice, sodium azide